Social safety nets and new venture performance: The role of employee access to paid family leave benefits - Bao, Jiayi (Strategic Management Journal, 2022)
Abstract Research Summary This study examines how social safety nets providing paid family leave (PFL) benefits to employees influence subsequent business performance for entrepreneurial ventures. A multilevel framework guided by qualitative interviews proposes two competing mechanisms (pre‐hiring recruitment gains via prospective employees and post‐hiring operation losses via incumbent employees) and a firm‐level contingency (venture innovation type). Leveraging the 2009‐implemented New Jersey PFL program in a difference‐in‐differences design, I show that employee access to state‐provided PFL benefits adversely affects the profitability for noninnovative new ventures but increases profitability for innovative ventures. Exploration of treatment timing and intermediate venture outcomes supports a dominating pre‐hiring mechanism for innovative ventures (in which the ventures become more attractive to joiners) but a dominating post‐hiring mechanism for noninnovative ventures (due to employee leave). Managerial Summary What are the business implications of employee access to paid family leave (PFL) benefits for nascent firms? Leveraging evidence from a U.S. state PFL program, the study shows that employee access to state PFL benefits hurts the profitability of noninnovative ventures but increases the profitability of innovative ventures. Results suggest that while noninnovative ventures experience operation losses as incumbent employees increase family leave use or quit their jobs, innovative ventures reap recruitment gains by attracting more and better prospective employees. For founders and managers, the provision of employee benefits is more central to firms' ability to create superior human capital pools than often thought and should be aligned with organizational incentive design and HR systems to prepare for productivity shocks related to employee leave use.